Multilateralism and the United Nations Security Council
XXII, 335 p. 29 illus., 19 illus. in color.
Keywords: This edited volume aims to address the gaps in research on the United Nations (UN)'s participation in intergovernmental relationships by delving into the working mechanisms of the United Nations Security Council (UNSC). The book offers a novel overview of the voting procedures of the UNSC and related outcomes in practice; most significantly, it examines members' voting behaviour, veto power, power dynamics, and diplomatic means of sponsoring resolutions and forming coalitions in the Council. It also analyses the role of small, emerging, and regional powers inside the UNSC, alongside their trajectory into the power dynamics of this UN body. It assesses the intertwined relationship between the UN and the European Union (EU). Each chapter demonstrates the challenges and the workings of multilateralism in one of the most significant organisations for global cooperation. Madeleine O. Hosli is a Professor of International Relations at Leiden University, Netherlands. Her main research interests are in international organization, international political economy and European integration. Gabriela Meneghetti Godinho Bueno is a Program Assistant for the Advanced MSc International Relations and Diplomacy program at Leiden University, Netherlands, and a Research Assistant for the Summer School 'The EU, the UN, and Global Governance.' Her research focuses on historical memories as a political tool in multilateralism. Katyayni Champawat recently earned her Master’s degree in International Relations and Diplomacy from Leiden University, Netherlands, following her Bachelor’s degree in History from Lady Shri Ram College, Delhi University, India. Passionate about research, writing, and editing, she aspires to further build a career in ecofeminism, feminist foreign policy, poststructuralism, and ontological security. Sofia Pires Lopes holds an Advanced Master of Science in International Relations and Diplomacy from Leiden University, Netherlands, and a Bachelor in Political Science and International Relations from Nova University of Lisbon in Portugal. She is passionate about Foreign Policy Analysis, Policy Change, and Gender issues.